2015
DOI: 10.5465/ambpp.2015.194
|View full text |Cite
|
Sign up to set email alerts
|

Desperately seeking fixedness: Practitioners’ accounts of ‘becoming doctoral researchers’

Abstract: We draw upon the concept of liminality to explore the experiences of practitioners enrolled on a UK Doctor of Business Administration (DBA) programme. We analyse twenty practitioners' reflective journals to detail how the DBA liminal space was negotiated. More specifically, we describe how practitioners deal with their struggles of identity incoherence or 'monsters of doubt' which are amplified in the DBA context owing to the complex nature of the separation phase of liminality. We identify three broad methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 11 publications
0
31
1
Order By: Relevance
“…From different theoretical perspectives, research on identity in liminal contexts has identified how people take different identity positions to create or maintain identity stability (Hay & Samra‐Fredericks, ; Ibarra & Obodaru, ). We argue that participants’ constructions of continuous selves serve as responses to unstable and sometimes identity‐threatening liminal contexts (Bamber et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From different theoretical perspectives, research on identity in liminal contexts has identified how people take different identity positions to create or maintain identity stability (Hay & Samra‐Fredericks, ; Ibarra & Obodaru, ). We argue that participants’ constructions of continuous selves serve as responses to unstable and sometimes identity‐threatening liminal contexts (Bamber et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the literature on liminal identity work is situated within organizational research such as human relations and management studies (e.g., Bamber, Allen‐Collinson, & McCormack, ; Daskalaki & Simosi, ; Hay & Samra‐Fredericks, ; Ibarra & Obodaru, ). This body of literature largely focuses on individuals whose career paths have been disrupted or renewed, and examines their identity work amidst or in the aftermath of these changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A nascent line of inquiry in management learning has begun to explore the experience of liminality inherent in how learners engage with threshold concepts (Hawkins & Edwards, 2015;Hay & Samra-Fredericks, 2016). Liminality is a concept from social anthropology that defines the temporal phase and social space in the middle of a ritual and involves a sense of being 'betwixt and between' (Turner, 1977;Van Gennep, 1960).…”
Section: Liminality and Threshold Concept Learningmentioning
confidence: 99%
“…In the field of management learning, some scholars have focused attention on threshold concepts and the modalities they create for teaching and learning in domains like leadership practice (Yip & Raelin, 2012), introductory management (Wright & Gilmore, 2012), and business ethics (Hibbert & Cunliffe, 2015). Other scholars have elaborated threshold concepts through their situatedness within a liminal process in which learners progress through an in-between state of doubt and uncertainty to a new transformed understanding (Hawkins & Edwards, 2015;Hay & Samra-Fredericks, 2016).…”
Section: Introductionmentioning
confidence: 99%